1992
DOI: 10.1088/0963-0252/1/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced fluorescence measurements on the C2Sigma+-X2IIrtransition of the CH radical produced by a microwave excited process plasma

Abstract: laserinduced fluorescence (UF) measurements were made in a micrwave (2.45GHz) excned a-C:H deposnion plasma using thew beam of a frequencydoubled cw dye laser. Miscellaneous vibrational and rotational transitions d the electronically acned CH band system C%+-X%, at X z= 314nm were investigated. Spatially resolved rdatlonal, vibrational and translational temperatures as well as driR velocnies and denskies cd ground state CH molecules have been determined. The most impatant mlewlar constants for the transnions u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…There are several low-pressure methods that have been used to deposit DLC films, including microwave plasmas, , electron-cyclotron resonance (ECR) plasmas, , dc-arcjet discharges, , and inductively coupled plasmas (ICPs). , The material properties of films deposited by these techniques are usually dependent on the plasma parameters, which implies that different plasma species play a key role in film growth. Numerous studies have, therefore, been performed on plasma reactions and on the gas-phase densities of the different species in methane-based plasmas. During the deposition processes, neutral hydrocarbon species are considered to be important precursors for film growth and have been widely studied . Luque et al have examined CH radicals in the CH A 2 Δ ← X 2 Π transition of a dc-arcjet discharge by laser-induced fluorescence (LIF) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several low-pressure methods that have been used to deposit DLC films, including microwave plasmas, , electron-cyclotron resonance (ECR) plasmas, , dc-arcjet discharges, , and inductively coupled plasmas (ICPs). , The material properties of films deposited by these techniques are usually dependent on the plasma parameters, which implies that different plasma species play a key role in film growth. Numerous studies have, therefore, been performed on plasma reactions and on the gas-phase densities of the different species in methane-based plasmas. During the deposition processes, neutral hydrocarbon species are considered to be important precursors for film growth and have been widely studied . Luque et al have examined CH radicals in the CH A 2 Δ ← X 2 Π transition of a dc-arcjet discharge by laser-induced fluorescence (LIF) .…”
Section: Introductionmentioning
confidence: 99%
“…The roles of gas-phase radicals and gas−surface interactions during film growth processes are important to understand overall methane plasma chemistry. For example, Kuedell and co-workers have investigated the simultaneous interaction of CH 3 and H radicals with amorphous, hydrogenated carbon (a-C:H) films using optical in-situ diagnostics. , They found that the sticking coefficient of CH 3 radicals is related to the surface radical site or “dangling bond” density. These sites are created by H radicals through abstraction of surface hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…c MCSCF does not converge for this state. The MCSCF core orbitals 1σ 2 g and 1σ u from another converged relevant state [8] (1σ 2 g 1σ u 3σ g ) were used as a zero-order wavefunction, and the remaining nine OEDOs were varied.…”
Section: Grammentioning
confidence: 99%
“…This paper deals with the computation of the two-centre electronic structure, which is of continued interest, both in terms of understanding recently discovered transitions (see, for example, [1]) and in terms of applications, such as new lasers, plasma, air glow studies (see, for example, [2][3][4]). Except for the usual treatment in terms of analytic basis functions, in the Born-Oppenheimer approximation, the two-centre electronic structure can be solved numerically in spheroidal prolate coordinates.…”
Section: Introductionmentioning
confidence: 99%